International Capital Mobility and Financial Integration: The Asia Pacific Perspective - Chan, Tze Haw (2001)
This study is conducted to examine the extent of capital mobility and financial integration in the Asia Pacific region. First, the Feldstein-Horioka approach is adopted to determine the capital mobility among the US, Japan and eight Asia Pacific countries. Second, the Real Interest Parity is employed to examine the financial integration amongst these countries. To capture the effect of financial liberalisation on these countries, the sample period is divided into two sub-periods, the pre-(1971:Q 1- 1983:Q4) and the post-liberalisation era (1984:Ql-2000:Q3). All empirical evidences are demonstrated through the application of cointegration tests, Granger-causality, Variance Decompositions (VDCs) and Impulse Response Functions (IRFs). The indications of non-co integrated and inactive of causality chains of saving investment relationships have provided sufficient evidence for the high capital mobility for all studied countries (including the United States and Japan) in both long run and short run. These findings are thus not supporting the argument which claimed that the saving-investment relationship is only applicable for small open countries. Hence, the failure of most previous researchers to establish such results may therefore reflect the method used rather than any inherent deficiency in the saving-investment relationship. Moreover, improper treatment of non-stationarity variables may yield results that are less favourable to long run relationship between the two aggregates. Results of real interest parity have indicated the dynamic causal linkages and greater financial integration amongst Asia Pacific countries during the post-liberalisation era. Relative active Granger-causal chains and the VDCs results have also demonstrated that ASEAN-5 are more interdependent among themselves as compared to the whole region. In addition, Singapore is found statistically endogenous in the multivariate system during post liberalisation, for both ASEAN-5 and the Asia Pacific-l0 model. This would imply that Singapore has been a vulnerable (to the world market) but very competitive and efficient financial centre since 198 0s. Moreover, the results of VDCs and IRFs have confirmed that the movements of real interest rates in Asia Pacific countries are mainly driven by both the US and Japan. However, the US market has much more dominance power than Japan, implying that Japan has not overtaken the role of US in the Asia Pacific regional financial market. Increased capital mobility and high regional financial integration have always entailed with large capital inflows into the developing Asia Pacific countries. Despite the potential welfare gained, capital inflows are most likely associated with monetary and price instability, contagion effects and speculative investments. Hence, the capital coping strategies and capital market restructuring will be the key interest for regional policy makers. Also, to provide a collective defense mechanism against systemic failure and monetary instability, this study proposes the Asia Pacific Optimal Currency Area.